Environmental profile of an innovative household biowaste dryer system based on Life Cycle Assessment. Issue 1 (January 2019) - Konstantzos, Giorgos E; Malamis, Dimitrios; Sotiropoulos, Aggelos; Loizidou, Maria
An alternative approach to biowaste management involves the application of an innovative household dryer for the dehydration of biowaste at source, in order to significantly reduce its mass and volume, and subsequently the collection frequency. The main objective of this work is to assess the potential impacts of the system under examination, which involves the household dryer use and kerbside collection of the dehydrated residues (biomass), by conducting a Life Cycle Assessment study. The stages considered in the present study include the following: (a) the construction of the household biowaste dryer; (b) the use of the dryer and the collection of dehydrated residues; (c) the end-of-life treatment of the dryer. The results revealed that emissions coming from kerbside collection account for the vast majority of the total emissions from each category examined, apart from Terrestrial Ecotoxicity, where lignite, heavy fuel oil and diesel combustion during electricity production affect mainly this category. The potential impact in Global Warming over 100 years was estimated to be 8.87 kg CO2 eq / t biowaste. The Human Toxicity Potential was 1.86 kg 1, 4-DB eq / t biowaste, Terrestrial Ecotoxicity Potential was 0.027 kg 1, 4-DB eq / t biowaste, Freshwater Aquatic Ecotoxicity Potential was 0.0126 kg 1, 4-DB eq / t biowaste and Marine Aquatic Ecotoxicity Potential was 521.85 kg 1, 4-DB eq / t biowaste. Acidification Potential was estimated at 0.035 kg SO2 eq / t biowaste, while Eutrophication Potential was 0.0065 kg PO4— eq / t biowaste. Finally, Photochemical Oxidation Potential was 0.0014 kg C2 H4 eq / t biowaste.